Chaperone regulation of biomolecular condensates - Bard, Jared A. M.; Drummond, D. Allan (Frontiers in Biophysics, 2024)
Biomolecular condensation allows for the dynamic organization of molecules in time and space. Condensate formation is regulated through many mechanisms including the action of molecular chaperones. While molecular chaperones have long been viewed through the lens of their roles in protein folding, misfolding, and quality control, their ability to manipulate protein-protein interactions is increasingly recognized to play a major role in the precise control of condensate biology. In this review we highlight recent studies investigating the roles of canonical and non-canonical chaperones in regulating condensate formation, material state, and dispersal. We discuss the broadening of longstanding conceptions of chaperone functions to include condensate regulation, and the discovery of previously unappreciated chaperone activities in well-known proteins. We close by considering the biological activities being uncovered during the ongoing upheaval at the boundary between chaperone biology and biomolecular condensation.